Microglia targeting by adeno-associated viral vectors - Stamataki, Maria; Rissiek, Björn; Magnus, Tim; Körbelin, Jakob (Frontiers in Immunology, 2024)
Microglia play a crucial role in maintaining homeostasis of the central nervous system and they are actively involved in shaping the brain's inflammatory response to stress. Among the multitude of involved molecules, purinergic receptors and enzymes are of special importance due to their ability to regulate microglia activation. By investigating the mechanisms underlying microglial responses and dysregulation, researchers can develop more precise interventions to modulate microglial behavior and alleviate neuroinflammatory processes. Studying gene function selectively in microglia, however, remains technically challenging. This review article provides an overview of adenoassociated virus (AAV)-based microglia targeting approaches, discussing potential prospects for refining these approaches to improve both specificity and effectiveness and encouraging future investigations aimed at connecting the potential of AAV-mediated microglial targeting for therapeutic benefit in neurological disorders.